Pengaruh Bystander Effect Terhadap Perilaku Kekerasan Bullying Pada Remaja Di Universitas Negeri Makassar - Andi Muhammad Yusran Atjo; Basti Tetteng (CV. Ulil Albab Corp, 2024)
This study aims to explore the effect of bystander effect on bullying violent behavior in adolescents at Makassar State University. The main focus of the study is to identify factors that influence the bystander effect on the occurrence of violent events in the campus environment. This study used two measurement instruments, namely the bystander effect scale and the bullying scale. The research sample consisted of 306 students of Makassar State University. Data were collected through questionnaires administered using purposive sampling techniques. Data analysis was conducted using relevant statistical techniques to identify the relationship between the bystander effect and bullying behavior in adolescents. The results showed that the significance score 0,00 (value under 0.05) showed a significant relationship between the bystander effect and bullying behavior in adolescents. In other words, participants who experienced the bystander effect tended to be more likely to engage in violent bullying behavior. These findings provide further understanding of the role of the bystander effect in the context of violent behavior among adolescents in the campus environment. This research makes an important contribution to understanding the dynamics of social interaction and the role of witnesses in cases of bullying violence in the university environment. The results of this study can be a foundation for developing more effective bullying prevention strategies and supporting the creation of a safe and friendly campus environment for all members.